Role of Design Audits in Reducing Errors and Rework: Lessons from Hong Kong - Palaneeswaran, E.; Love, Peter; Kim, J. (American Society of Civil Engineers, 2014)
Design audits have been identified as an effective mechanism for reducing errors and the subsequent rework that can arise during the construction process. Despite their effectiveness, errors and rework remain problematic issues as a result of ineffective audit protocols and systems.Drawing on experiences from Hong Kong, a triangulated research approach is adopted to examine how design audits can be effectively used to reduce errors and rework. With increasing schedule and fee pressures being imposed upon construction and engineering firms by theirclients, it is vital that engineering firms do not eschew tasks associated with the auditing process to ameliorate efficiency and maximize fees. The rework associated with addressing errors during construction not only increases project costs and the schedule, but also reduces an engineeringfirm’s profit and reputation. A systemic audit system for construction projects derived from experiences in Hong Kong, and which may also be considered in other countries, is presented